Fucoxanthin for Topical Administration, a Phototoxic vs. Photoprotective Potential in a Tiered Strategy Assessed by In Vitro Methods - Renata Spagolla Napoleão Tavares; Camila Martins Kawakami; Karina de Castro Pereira; Gabriela Timotheo do Amaral; Carolina Gomes Benevenuto; Silvya Stuchi Maria-Engler; Pio Colepicolo; Hosana Maria Debonsi; Lorena Rigo Gaspar (MDPI AG, 2020)
Fucoxanthin possesses a well-described antioxidant activity that might be useful for human skin photoprotection. However, there is a lack of scientific information regarding its properties when applied onto human skin. Thus, the objective of the present study was to assess the photoprotective and phototoxicity potential of fucoxanthin based on its ultraviolet (UVB 280-320 nm; UVA 320-400 nm) and visible (VIS 400-700 nm) absorption, photostability, phototoxicity in 3T3 mouse fibroblast culture vs. full-thickness reconstructed human skin (RHS), and its ability to inhibit reactive oxygen species formation that is induced by UVA on HaCaT keratinocytes. Later, we evaluated the antioxidant properties of the sunscreen formulation plus 0.5% fucoxanthin onto RHS to confirm its bioavailability and antioxidant potential through the skin layers. The compound was isolated from the alga Desmarestia anceps. Fucoxanthin, despite presenting chemical photo-instability (dose 6 J/cm2: 35% UVA and 21% VIS absorbance reduction), showed acceptable photodegradation (dose 27.5 J/cm2: 5.8% UVB and 12.5% UVA absorbance reduction) when it was added to a sunscreen at 0.5% (w/v). In addition, it increased by 72% of the total sunscreen UV absorption spectra, presenting UV-booster properties. Fucoxanthin presented phototoxic potential in 3T3 fibroblasts (mean photo effect 0.917), but it was non-phototoxic in the RHS model due to barrier function that was provided by the stratum corneum. In addition, it showed a significant inhibition of ROS formation at 0.01% (p < 0.001), in HaCat, and in a sunscreen at 0.5% (w/v) (p < 0.001), in RHS. In conclusion, in vitro results showed fucoxanthin protective potential to the skin that might contribute to improving the photoprotective potential of sunscreens in vivo.